2019
DOI: 10.1111/cup.13581
|View full text |Cite
|
Sign up to set email alerts
|

White sponge nevus: A condition not always clinically suspected

Abstract: White sponge nevus (WSN) is an uncommon benign inherited disorder characterized bywhite and diffuse painless lesions in oral, esophageal, or genital mucosa. The lesions may develop at birth or later in childhood or adolescence, with careful clinical examination being sufficient for diagnosis in most cases. However, microscopic analysis may be necessary particularly in adults in which other whitish oral lesions may be clinically suspected.Dermatologists, dentists, and pathologists should consider WSN when evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…Cells within the spinous layer often display perinuclear eosinophilic condensation of the cytokeratin filaments 3 . Our patient presented with perinuclear eosinophilic condensations, as well as hyperparakeratosis, acanthosis, and vacuolization of the suprabasal layers, all of which been reported as histopathological findings of WSN 6 …”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…Cells within the spinous layer often display perinuclear eosinophilic condensation of the cytokeratin filaments 3 . Our patient presented with perinuclear eosinophilic condensations, as well as hyperparakeratosis, acanthosis, and vacuolization of the suprabasal layers, all of which been reported as histopathological findings of WSN 6 …”
Section: Discussionsupporting
confidence: 49%
“…5 For this reason, biopsy is often warranted to confirm the diagnosis. 6 However, there is no evidence at this time that WSN develops dysplastic change or causes predilection to cancers of the oral cavity. 5…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another report was published by Hegde et al in 2017 [12]. In 2020, Bezerra et al reported cases of WSN demonstrating it as a condition that is not always clinically suspected [13].…”
Section: Discussionmentioning
confidence: 99%